Antarctic Cities and the Global Commons: Rethinking the Gateways - (:unkn) unknown (My University, 2025)
This project aims to investigate how the Antarctic 'gateway cities' of Hobart, Australia; Christchurch, New Zealand; and Punta Arenas, Chile might reimagine and intensify their relations to the continent and each other. As pressures on Antarctica increase, these 'gateway cities' will become critical to its future. This research is expected to create a robust custodial network of partner organisations that helps these cities care for Antarctica.